Immune characterization of the Lewis rats inoculated with K2 sarcoma cell line and newly derived R5-28 malignant cells - Morávková, A; Málek, O; Pokorná, E; Strnádel, J; Hradecký, J; Horák, V (Folia biologica, 2005)
Sarcoma is a relatively rare malignant disease with high mortality, bad prognosis and response to conventional therapy. Two possible models of this disease were tested: the K2 rat sarcoma cell line, which was described previously, and the new rat R5-28 cell line derived from a spontaneously growing rat neoplasm with sarcoma morphology. While all rats inoculated with K2 cells developed tumours at 22th-25th day after inoculation (D = 22-25), only 60%-75% of R5-28-inoculated rats were affected by tumours. The frequency and progress of the disease depended on the number of inoculated cells. No metastases were detected in both cases. All affected animals showed large splenomegaly. A possible response of some immune system components to tumours was tested. No tumour-infiltrating lymphocytes were revealed in the tumour tissue. Anti-tumour antibodies were not found in tumour-bearing animal sera. Appropriate changes in peripheral blood lymphocyte subsets were explored. While the relative numbers of both NK cells and Tc were impaired, no changes were noted in numbers of CD4+CD8- T helper cells. Leukocytosis with highly increased numbers of CD11b+ myeloid cells displaying variable expression of CD4 was detected in terminal stages of the disease.
Keywords: nádorové buněčné linie; Rats; podskupiny lymfocytů; Neoplasm Transplantation; mužské pohlaví; prekurzorové buňky granulocytů; Lymphocyte Subsets; Cell Line, Tumor; krysa rodu Rattus; experimentální sarkom; ženské pohlaví; zvířata; Granulocyte Precursor Cells; transplantace nádorů; potkani inbrední LEW; Sarcoma, Experimental; Rats, Inbred Lew; Female; Male; Animals